Identification and genetic diversity of Japanese apricot (Prunus mume) accessions in northern Vietnam - THI TUYET CHAM LE; THI MAI ANH VU; THI THUY HANG VU; THI NGOC PHAM; DANG DUNG HOANG; THU THUY DOAN (Society for Indonesian Biodiversity, 2025)
Abstract. Le TTC, Vu TMA, Vu TTH, Pham TN, Hoang DD, Doan TT. 2025. Identification and genetic diversity of Japanese apricot (Prunus mume) accessions in northern Vietnam. Biodiversitas 26: 2383-2392. Japanese apricot (Prunus mume) is a valuable stone fruit crop grown in northern Vietnam, but lacks comprehensive identification and genetic diversity data. This study aimed to identify species and assess the genetic diversity of Japanese apricot accessions from these regions. A rigorous of agro-morphological traits and ycf1 sequence analysis was applied to identify P. mume plants. The genetic diversity of these 30 collected P. mume accessions was analyzed using 19 SSR markers, ensuring a comprehensive understanding of the species. The agro-morphological comparison showed that the Japanese apricot was distinguished from the closely related species (Prunus salicina) in several characteristics, including a later flowering time, shorter leaf length, smaller fruit size, and lower flesh rate, but higher Brix. Sequence alignments of the ycf1 gene revealed that the Japanese apricot differed from close species by nine autapomorphic characters and clustered within the P. mume clade. Microsatellite analysis for the 30 P. mume accessions exhibited a moderate polymorphism (PIC = 0.41). PCoA and STRUCTURE analysis grouped 30 accessions into NM (18 accessions) and RD (12 accessions) populations according to geographic origin. In summary, the Japanese apricot was recognized as a P. mume species, and 19 SSR markers are informative for assessing the Japanese apricot's genetic diversity in Vietnam.